Factors Affecting Quality of Life in Chronic Kidney Failure Patients Receiving Hemodialysis - Johan Budhiana; Rosliana Dewi; Nurul Novtiana Sabilah; Nurvita Trianasari; Abdul Rahman La Ede (JHeS (Journal of Health Studies), 2022)
The quality of life of CKD patients receiving hemodialysis may be impacted by the development of clinical symptoms. Family support, self-efficacy, and coping methods are a few things that have an impact on quality of life. The goal of the study was to ascertain how coping strategies, self-efficacy, and family support affected quality of life. This kind of research uses a cross-sectional strategy and is correlational. The population consists of hemodialysis patients with chronic renal failure, and a complete sampling technique was used with a sample size of 71 individuals. Questionnaires and path analysis are two methods used in data collection. The mean family assistance, according to research findings, is $55.00. Self-efficacy scores on mean are 72.14, coping skills scores on mean are 40.35, and quality of life scores on mean are 62.76. The quality of life is influenced by family support (p = 0.013), self-efficacy (p = 0.002), and coping techniques (p = 0.000). The quality of life of people with chronic kidney failure is influenced by family support, self-efficacy, and coping methods. The hospital should be able to do more to enhance quality of life and health promotion.